ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAH TERHADAP ASET TETAP PEMERINTAH DAERAH KABUPATEN BOLAANG MONGONDOW - Lauma, Enda Baisida; Morasa, Jenny; Kalangi, Lintje (Universitas Sam Ratulangi, 2016)
Government Accounting Standard have changed from Cash Basis is to comply with the Government Regulation number 24 2005s to Government Regulation number 71 2010s. Requirement to implemented Accrual basis SAP by the Local Government was start in the Local Government Financial Statement for the year ended on December 2015s. The District Government of Bolaang Mongondow, before implemented accrual basis PP 71/2010 always received non-WTP opinion, because of asset problems. The objective of the research is to analyze the implementation of Government Accounting Standard to Fix Asset on the District Government of Bolaang Mongondow. The result of research indicate that although the District Government of Bolaang Mongondow has implemented the SAP based on accrual basis on this fix assets based on regulation (PP 71/2010) at Local Government Financial Statement Budget Year 2015s, it is found that financial statement still have constraints such differences in recording those assets between accounting division and assets division. In addition, there is non-current asset which do not master by SKPD, there is no information regarding existing assets, and some assets are also not clearly described. Those constraints have caused to gain Qualified Opinion of LKPD 2015s as audited by BPK. Keywords : Implementation, Governmental Accounting Standard, Fix Asset.